Experimental investigations on transient flow and heat transfer characteristics of RP-3 at supercritical pressure. (August 2022) - Wu, Kun; Feng, Yu; Li, Deshi; Xu, Shuai; Qin, Jiang; Huang, Hongyan
Highlights: Thermal response characteristics due to step perturbation has been investigated. Flow and heat transfer have almost the same response time. Thermal response time would decrease as initial temperature increase. Heat transfer Deterioration would lead to the thermal response time increase. Abstract: Variable operation conditions due to the wide speed range of hypersonic vehicles are complicated and are often related to the heat load change of the chamber wall. Thermal and flow response characteristics during flight state change are investigated in this research experimentally by utilizing the electrically heating experiment system. It is revealed that the response time of flow and heat transfer due to step perturbation is longer than that of perturbation. The response time decreases as the initial temperature increases when the fuel temperature is lower than the critical temperature. Once the temperature is higher than critical temperature, the response time begins to increase as the initial temperature increases. A 3D transient model is adopted to help to explain this phenomenon. The results indicate that the reason for the characteristics is the weakening of heat diffusion near the wall due to heat transfer deterioration. This conclusion is beneficial to the regulation of the coolant.